Tinjauan Fiqh Muamalah Terhadap Transaksi Jual Beli Perhiasan Emas Dengan Cara Tukar Tambah Di Pasar Pagi Kota Samarinda (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
Maslahul Ihsan, 2018. Overview of Muamalah Fiqh About Buying and Selling Gold Jewelry by Swapping by Adding Exchange at Pasar Pagi Gold Shop Samarinda City. With guidance from Mr Muhammad Saleh as the first mentor and Rabiatul Adawiyah mother as the second mentor.The problem statement in this thesis is the practice of buying and selling gold jewelry by way of trade-in the Pasar Pagi of Samarinda City and the practice of buying and selling gold jewelry that is in accordance with muamalah fiqh. This thesis uses a research method with a type of field research. The data source of this research is gold sellers and buyers as primary data and secondary data taken from books, articles and internet data and literature related to this thesis. The research technique used is observation, interviews and documentation. Data analysis techniques using a qualitative descriptive approach.The results of the study the practice of adding gold jewelry in four gold shops in the Pasar Pagi of Samarinda City. In practice consumers come with gold jewelry that has been used with the intention of buying new jewelry in accordance with what consumers want with different sizes and there are also exchanges with same-sex and size, without any submission of proceeds from the sale of old gold then the payment method is different of the two prices and also there are additional costs given by two shop owners to consumers, namely as a cost of cleaning and gilding costs of Rp. 20,000/gram and there is also Rp. 25,000/gram.